2012
DOI: 10.1590/s0100-736x2012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation and use of gamma interferon assay for the diagnosis of bovine tuberculosis in Brazil

Abstract: This study aimed to evaluate the interference of tuberculin test on the gamma-interferon (INFg) assay, to estimate the sensitivity and specificity of the INFg assay in Brazilian conditions, and to simulate multiple testing using the comparative tuberculin test and the INFg assay. Three hundred-fifty cattle from two TB-free and two TB-infected herds were submitted to the comparative tuberculin test and the INFg assay. The comparative tuberculin test was performed using avian and bovine PPD. The INFg ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Both tests were very specific, with small variations between herds and within herds. Also, specificities estimates were close to those already reported in the literature (Lopes et al, 2012;Casal et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both tests were very specific, with small variations between herds and within herds. Also, specificities estimates were close to those already reported in the literature (Lopes et al, 2012;Casal et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Bayesian latent class models had already been used before to evaluate diagnostic tests for bovine tuberculosis (Álvarez et al, 2012;Lopes et al, 2012). However, it had never been done before for this commercial serological test, aimed to diagnose bovine tuberculosis in Brazil using BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Brazil, kappa values were 0.54-0.66 depending on time points when the IFN-γ assay (Bovigam, criteria for the IFN-γ assay not provided) was performed. Agreement increased to 0.649-0.713 when data from cattle affected by M. avium complex were withdrawn (23). A study performed in Ireland in 2015 showed relatively higher agreement between the single intradermal comparative tuberculin test and IFN-γ assay (Bovigam, cutoff for the INF-γ assay = 0.05) (20).…”
Section: Discussionmentioning
confidence: 99%
“…A longer storage or transportation of the blood samples might lead to a decrease in the mean OD or the IFN-ɣ production [ 73 75 ]. With regard to the sensitivity and specificity of the Bovigam® assay several studies state that blood could also be processed 24 h later without statistical significant changes [ 76 , 77 ]. However, Laboratory 3 reached also only a substantial agreement of 0.62 between the Bovigam® assay test results of the V .…”
Section: Discussionmentioning
confidence: 99%